Prevalence, Spectrum, and Outcomes of Single Coronary Artery Detected on Coronary Computed Tomography Angiography (CCTA) - Rashid Al Umairi; Maryam Al-khouri (Radiology Research and Practice)
Background. Single coronary artery (SCA) is a rare congenital anomaly in which there is an isolated coronary artery that arises from a single coronary ostium and provides coronary blood supply to the entire myocardium. SCA is classified into different types based on the origin, branching pattern, and course. Although the majority of patients with SCA are asymptomatic, some patients can present with life-threatening symptoms. Aim. To examine the prevalence, anatomical distribution, and outcome of the single coronary artery anomaly detected on coronary computed tomography angiography (CCTA) in a single center in Oman. Methods. Retrospectively, we reviewed 4,445 patients who underwent coronary computed tomography angiography between September 2012 and August 2018 at the National Heart Center, Muscat, Oman. We identified patients with a single coronary artery, and we evaluated the origin, course, and outcome of SCA. Results. We found 12 patients with single coronary artery among 4,445 patients with a mean age of 56.4 years (age range: 34 to 71 years; male : female ratio: 5 : 7). The most common class was RIII-C seen in 4 patients. Other SCA included RII-C, RII-A, and RII-S, two in each class. One patient had RI and one had LII-P. Two patients had coronary artery bypass graft. No major adverse cardiac events were reported over a mean follow-up of 25.3 months. Conclusion. Single coronary artery (SCA) is a rare congenital anomaly classified into different types. In our study, the prevalence of SCA was 0.27% that is higher than the figures from previous reports.